2017
DOI: 10.1038/ncomms14096
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenation of iron in the early stage of Earth’s evolution

Abstract: Density of the Earth's core is lower than that of pure iron and the light element(s) in the core is a long-standing problem. Hydrogen is the most abundant element in the solar system and thus one of the important candidates. However, the dissolution process of hydrogen into iron remained unclear. Here we carry out high-pressure and high-temperature in situ neutron diffraction experiments and clarify that when the mixture of iron and hydrous minerals are heated, iron is hydrogenized soon after the hydrous miner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 42 publications
1
46
1
1
Order By: Relevance
“…A monochromatic incident X‐ray beam was collimated to 6 μm (full width at half maximum). Since hydrogen escapes from solid Fe during decompression to 1 bar (Fukai & Suzuki, ; Iizuka‐Oku et al, ; Okuchi, ), hydrogen concentration in quenched liquid alloy was estimated from the volume of FeH x at high pressure and 300 K, which appeared upon quenching temperature (Figure S1 in the supporting information). The hydrogen content, x in FeH x , can be obtained x=()VFeHitalicxVFe/normalΔVH in which V Fe is the volume of Fe (Dewaele et al, ) and Δ V H is the volume increase per hydrogen atom.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A monochromatic incident X‐ray beam was collimated to 6 μm (full width at half maximum). Since hydrogen escapes from solid Fe during decompression to 1 bar (Fukai & Suzuki, ; Iizuka‐Oku et al, ; Okuchi, ), hydrogen concentration in quenched liquid alloy was estimated from the volume of FeH x at high pressure and 300 K, which appeared upon quenching temperature (Figure S1 in the supporting information). The hydrogen content, x in FeH x , can be obtained x=()VFeHitalicxVFe/normalΔVH in which V Fe is the volume of Fe (Dewaele et al, ) and Δ V H is the volume increase per hydrogen atom.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…in Fukai & Suzuki, ). It has been repeatedly reported that hydrogen goes away from solid Fe when it transforms into the body‐centered cubic phase upon decompression (Iizuka‐Oku et al, ; Okuchi, ). The melting temperature in the Fe‐H system is similar to that of pure Fe at 1 bar (Fukai et al, ), which means that hydrogen is neither soluble in solid nor liquid Fe at ambient pressure and therefore indicates that hydrogen originally included in iron under high pressure escapes during pressure release.…”
Section: Introductionmentioning
confidence: 99%
“…The dissolution of hydrogen into metal droplets would have been isotopically selective, fractionating the hydrogen isotopes. Owing to the instability of iron hydrides at the low pressures at which mass spectrometry is possible, no measurements of this fractionation have been successful (Iizuka‐Oku et al, ). However, based on hydrogen dissolution into proxies at low pressures, we expect the light isotopes of hydrogen to have been selectively taken up by the metal.…”
Section: Hypothesismentioning
confidence: 99%
“…Hydrogen can be incorporated into minerals in highly variable amounts. Once incorporated, the hydrogen is circulated throughout the Earth, from the surface to the deep interior, affecting the long-term evolution of the planet (Iizuka-Oku et al, 2017;Kawakatsu & Watada, 2007;Okuchi, 1997;Thompson, 1992). A major proportion of this hydrogen is currently stored within the crystal structures of dense minerals that are thermodynamically stable under the high pressures and temperatures of the deep mantle of the Earth (Ohtani, 2015;Purevjav et al, 2014Purevjav et al, , 2016Purevjav et al, , 2018Sano-Furukawa et al, 2018).…”
Section: Introductionmentioning
confidence: 99%